Effect of bioactive compounds on enzymatic regulation and shelf life of mango during post-harvest - Balachandran, Adarsh; Sivakumar, V; Kavitha, C; Giridhari, V Veeranan Arun; Rajavel, M (Plant Science Today, 2025)
The effects of melatonin, salicylic acid (SA) and brassinosteroids on the post-harvest quality and shelf life of two mango varieties, Alphonso and Sindhura, were investigated with respect to physiological, biochemical and enzymatic changes. The study assessed physiological loss in weight (PLW), Total Soluble Solids (TSS), titratable acidity, sugars, total phenolics, carotenoids, ripening related enzymes (pectin methylesterase, polygalacturonase, amylase and cellulase) and antioxidant enzymes (peroxidase, catalase and superoxide dismutase). According to the results, the shelf life of mango was considerably increased by 200 µM melatonin, 2.0 mM salicylic acid and 25 ppm brassinosteroids, which also decreased PLW to 9.81%, 10.12% and 9.79% in Alphonso and 9.48%, 9.51% and 9.92% in Sindhura. These treatments maintained a balance between TSS, sugars and acidity, while preserving higher concentration of total phenolics and carotenoids. Treated fruits exhibited lower ripening enzyme activity, particularly polygalacturonase, which declined by 16.7%, 11.2% and 17.0% in Alphonso and 11.5%, 10.9% and 11.2% in Sindhura with 200 µM melatonin, 2.0 mM salicylic acid and 25 ppm brassinosteroids treatments respectively. Similarly, pectin methyl esterase (PME) was reduced by 12.2%, 11.6% and 10.5% in Alphonso and 12.1%, 10.3% and 12.1% in Sindhura corresponding to these treatments, delaying cell wall degradation and maintaining fruit firmness. Additionally, antioxidant enzymes were upregulated, mitigating oxidative stress by reducing reactive oxygen species (ROS) and preserving fruit quality. These treatments were effective in delaying ripening, enhancing stress resistance and extending the marketability of mangoes during storage. This study highlights the potential of melatonin, salicylic acid and brassinosteroids as eco-friendly alternatives to synthetic chemicals for improving post-harvest mango management.